EDUKASI DAN PENERAPAN PENGELOLAAN SAMPAH BERBASIS ZERO WASTE SKALA RUMAH TANGGA DI DESA COT GUD - Silviana, Mery; Amalia; Lindawati; Haiqal, Arya (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Cot Gud Village is a village in Aceh Besar Regency, where waste management is still carried out conventionally, especially by collected and taken to a landfill or destroyed by burning. This form of waste disposal is not environmentally favorable, especially to the air that humans breathe. One strategy to overcome this problem is the zero-waste concept approach, a waste management strategy with the aim of reducing or eliminating the amount of waste produced by households by recycling. The purpose of this community service activity is to educate residents of Cot Gud Village in waste management with the zero-waste concept. This activity was carried out using the socialization method and application of household-scale bio pores which was carried out in September 2024 in Cot Gud Village, consisting of two socializations, namely: 1) socialization of organic and inorganic waste sorting as an initial movement of the zero waste-based waste management concept, and 2) socialization of waste management with the zero waste concept using the bio pore method, specifically by a tool made of PVC pipes and modified into a tool that can decompose household organic waste into compost that can fertilize the soil around the bio pores. From the evaluation results, it was found that residents already recognize the types of waste and how processing can be done on a household scale.